Learning and elucidating the uncertainty in primary care by mapping uncertainty in medicine - Yuma Ohtsuka; Kazuoki Inoue; Daisuke Son; Shinichi Taniguchi (Journal of General and Family Medicine)
This letter reports on a workshop aiming to ease clinical practice by mapping uncertainties in clinical practice. The workshop was indeed effective considering the mapped uncertainties based on previous research and included discussion. We believe that future expansion of similar activities will promote the study of uncertainty in clinical practice.